A Review of Physiology Concept of Mana - Ranawa, Yogeshwari; Sharma, Rajesh Kumar; Sharma, Dinesh Chandra (International Research Journal of Ayurveda & Yoga, 2022)
According to Indian thoughts, Manas (mind) is one of the major operational concepts in the process of learning and the cause of bandha (entanglement/attachment). Manas has dimension which is Anu(beyond atom in its minutest aspect), and is capable of remaining Atindriya (beyond sensory perception). An attempt has been made to focus on various aspects like concept of Atma, evolution and constituents of man, location of Manas, dimension and qualities of Manas and process of Jnanotpatti etc.